Experiences and needs of direct support staff working with people with intellectual disabilities during the COVID‐19 pandemic: A thematic analysis - Embregts, Petri J. C. M.; Tournier, Tess; Frielink, Noud (Journal of applied research in intellectual disabilities, 2021)
Background The present study aimed to explore the experiences and needs of direct support staff during the initial stage of the COVID‐19 lockdown in the Netherlands. Method Overall, eleven direct support staff were recruited from five intellectual disability services to participate in this descriptive qualitative study. They recorded 34 audio messages during the considered period. Thematic analysis was used to analyse these audio recordings. Results Four themes emerged: (1) Emotional impact, which pertained to various emotions they experienced in their work; (2) Cognitive impact, which referred to challenges and changes they had undergone in their work; (3) Practical impact, which centred on the practical impact of the pandemic on their work; and (4) Professional impact, which concerned their experiences with other professionals. Conclusions This study provides valuable insights into the experiences and needs of direct support staff during the COVID‐19 pandemic, which, in turn, can help inform practice in preparation for a second wave of COVID‐19 or another future pandemic.